ZORA 149: Slovenščina kot drugi in tuji jezik v izobraževanju (University of Maribor Press, 2022)
ZORA 149: Slovene as a Second and Foreign Language in Education. The scientific monograph Slovene as a second and foreign language in education brings peer-reviewed papers in which, due to the topicality and consequently increasing need for the Slovene as a non-native language acquisition, from the point of view of the modern didactic, linguistic, cultural and literary studies approaches, the meaning and role of Slovene as a second and foreign language should be presented in education. The authors are representatives of the Slovenian Academy of Sciences and Arts (SASA), the University of Maribor, the University of Ljubljana and the University of Primorska, as well as of institutions from Austria, Croatia, Hungary, the Czech Republic and Ukraine. The monograph was edited by Simona Pulko and Melita Zemljak Jontes from the Department of Slavic Languages and Literature, Faculty of Arts, University of Maribor. The legislation, inclusive in papers on immigrant students, is general and school-related. The first group (general-related legislation) includes international documents and general Slovene legislation: Ustava Republike Slovenije (2006), Resolucija o migracijski politiki Republike Slovenije (2002), Zakon o azilu (2006), Zakon o tujcih (2009, 2011) and Zakon o spremembah in dopolnitvah Zakona o tujcih (ZTuj-2F) (2021). The second group (school-related) includes the following documents: Bela knjiga o vzgoji in izobraževanju (2011), Zakon o osnovni šoli (2006), Zakon za uravnoteženje javnih financ (2012) and Pravilnik o preverjanju in ocenjevanju znanja (2013); also Strategija vključevanja otrok, učencev in dijakov migrantov v sistem vzgoje in izobraževanja v Republiki Sloveniji (2007), Smernice za izobraževanje otrok tujcev v vrtcih in šolah (2009), Smernice za vključevanje otrok priseljencev v vrtce in šole (2012), Vključevanje otrok priseljencev v slovenski vzgojno-izobraževalni sistem (2017), Predlog programa dela z otroki priseljenci za področje predšolske vzgoje, osnovnošolskega in srednješolskega izobraževanja (2018) and Pravilnik o spremembah in dopolnitvah Pravilnika o normativih in standardih za izvajanje programa osnovne šole (2019). Slovenia is also a signatory to the document Ključne kompetence za vseživljenjsko učenje: evropski referenčni okvir (UL EU 2018/C 189/8). Bela knjiga o vzgoji in izobraževanju (2011) is a document that contains the principles, goals and strategic orientations of education, primarily as general, then according to the levels of schooling (kindergarten, primary school, secondary school). A special chapter deals with the principles, goals and strategies related to immigrant children and children born in Slovenia whose mother tongue is not Slovene. The awareness of the use of languages in education is particularly important, i.e. Slovene as a first and second language, mother tongue and foreign languagee (2011: 33-35). Respect for all children whose mother tongue is not Slovene is manifested above all in the principle of promoting interculturality, as awareness of the common cultural heritage as the fundamental condition for accepting and respecting the pluralism of cultures. Discussions written from different research perspectives are oriented to the following thematic areas: Slovene as a second and foreign language in the Germanic, South Slavic, Romanic and Hungarian areals; Slovene literature on Slavic studies in the Germanic, South Slavic, Romanic and Hungarian areals; Slovene compared to typologically and genetically (un)related languages; the role of literary texts in teaching Slovene as a second and foreign language; the role of professional and popular science texts in teaching Slovene as a second and foreign language; textbook materials for teaching Slovene as a second and foreign language; bilingual and multilingual authors in teaching Slovene as a second and foreign language; modern approaches, methods and new technologies in the teaching and acquisition of Slovene as a second and foreign language (at primary and secondary schools and gymnasiums, at universities, etc.); Slovene cultural heritage in teaching Slovene as a second and foreign language; cultural and ecological themes in teaching Slovene as a second and foreign language; the role of areales in teaching Slovene as a second and foreign language.